Impact of Implementing a Pediatric Early Warning System (PEWS) in a Pediatric Oncology Hospital - Agulnik, Asya (Pediatr Qual Saf, 2018)
BACKGROUND: Hospitalized pediatric oncology and hematopoietic stem cell transplant (HSCT) patients have frequent clinical deterioration requiring transfer to the Pediatric Intensive Care Unit (PICU). Pediatric Early Warning Systems (PEWS) can aid early identification of clinical deterioration and improve outcomes in these patients. OBJECTIVES: Describe the impact of PEWS implementation in a dedicated pediatric hematology-oncology/HSCT hospital. METHODS: A PEWS tool and escalation algorithm were implemented between August and October 2016 (Fig. 1). Implementation quality was evaluated by measuring errors in PEWS calculation, omissions, and algorithm activation. Frequency of emergency activations and method of unplanned PICU transfer were compared before and after PEWS implementation. RESULTS: Random monitoring of PEWS scores demonstrated 12.7% calculation errors, 3.8% omissions, and 1.7% algorithm errors. Omissions and algorithm errors decreased over time following implementation (P < 0.0001 and P = 0.005, respectively). Frequency of Rapid Response Team (RRT) activations increased after PEWS implementation from 1.3 to 12.2/1,000-inpatient-days (P < 0.0001), without an increase in Code Blue activations (1.2 to 0.97/1,000-inpatient-days, P = 0.49, Fig. 2) and no change in frequency of unplanned PICU transfers (5.7/1,000-inpatient-days before and after PEWS implementation). Unplanned PICU transfers arriving via RRT increased from 11.5% to 60.5% of admissions (P < 0.0001, Fig. 3). CONCLUSIONS/IMPLICATIONS: PEWS can be successfully implemented in a pediatric hematology-oncology/HSCT hospital with improvement in accuracy over time. Implementation of PEWS resulted in increased use of the RRT system and more patients with clinical deterioration arriving to the PICU via an organized escalation pathway, representing standardization of care and improvement in the culture of safety in the hospital.